How to build a digital library - Witten, Ian H.; Bainbridge, David , 1969-; Nichols, David M. (The Morgan Kaufmann series in multimedia information and systems, 2010)
How to Build a Digital Library is the only book that offers all the knowledge and tools needed to construct and maintain a digital library, regardless of the size or purpose. It is the perfectly self-contained resource for individuals, agencies, and institutions wishing to put this powerful tool to work in their burgeoning information treasuries. The Second Edition reflects new developments in the field as well as in the Greenstone Digital Library open source software. In Part I, the authors have added an entire new chapter on user groups, user support, collaborative browsing, user contributions, and so on. There is also new material on content-based queries, map-based queries, cross-media queries. There is an increased emphasis placed on multimedia by adding a "digitizing" section to each major media type. A new chapter has also been added on "internationalization," which will address Unicode standards, multi-language interfaces and collections, and issues with non-European languages (Chinese, Hindi, etc.). Part II, the software tools section, has been completely rewritten to reflect the new developments in Greenstone Digital Library Software, an internationally popular open source software tool with a comprehensive graphical facility for creating and maintaining digital libraries." -- Publisher's description.